Parental Involvement Among Collegiate Student-Athletes - Katie Lowe; Travis E. Dorsch; Miranda P. Kaye; Jeffrey Jensen Arnett; Logan Lyons; Amanda N. Faherty; Lindsey Menendez (University of Kansas Libraries, 2018)
Despite emerging evidence of a link between parental involvement and student-athletes' (SA) experiences, and the desire for educational programming for parents of these SAs, previous research has been limited to the Division I level. This has prevented the ability to inform, develop, and deliver parent programming across the NCAA's diverse membership. The present study was designed to descriptively assess SA reports of parental involvement (i.e., support, contact, academic engagement, athletic engagement) across NCAA Division I, II, and III member institutions and examine the potential impact of this involvement on SAs' experiences (i.e., academic self-efficacy, athletic satisfaction, well-being, individuation). Participants were 455 SAs (53% female; 81% Caucasian; Mage = 19.81, SD = 1.65) from DI (30%), DII (37%), and DIII (33%) institutions, who completed an online survey with items assessing parental involvement and SA experiences. Regarding academic classification, 32% were freshmen, 24% sophomores, 22% juniors, and 22% seniors. Results provide novel evidence for an absence of division-wide differences in average levels of involvement and no variability in links between involvement and SA experiences across divisions. Results complement and extend previous research by offering a clearer understanding of differential associations between involvement and SAs' experiences regardless of division, notably that involvement bolstered well-being but also strongly detracted from individuation. Findings highlight the importance of developing programs to promote positive and developmentally-appropriate parental involvement across the spectrum of intercollegiate athletics, especially given the absence of evidence-based resources presently offered by the NCAA.